2010
DOI: 10.1158/0008-5472.can-10-0339
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nanoparticles That Deliver a Sustained, Specific Release of Paclitaxel to Irradiated Tumors

Abstract: To capitalize on the response of tumor cells to XRT, we developed a controlled-release nanoparticle drug delivery system using a targeting peptide that recognizes a radiation-induced cell surface receptor. Phage display biopanning identified Gly-Ile-Arg-Leu-Arg-Gly (GIRLRG) as a peptide that selectively recognizes tumors responding to XRT. Membrane protein extracts of irradiated glioma cells identified glucose-regulated protein GRP78 as the receptor target for GIRLRG. Antibodies to GRP78 blocked the binding of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 31 publications
(49 reference statements)
2
104
0
1
Order By: Relevance
“…Following the NPs arrival at the disease site in the body, the polymer matrix slowly degrades resulting in sustained release of the encapsulated therapeutic agents. Thus, the NPs have a dual capacity of drug targeting delivery and sustained release capability (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Following the NPs arrival at the disease site in the body, the polymer matrix slowly degrades resulting in sustained release of the encapsulated therapeutic agents. Thus, the NPs have a dual capacity of drug targeting delivery and sustained release capability (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally new approaches based in fluorescent labelled DDS are used for identification of dysplasia by molecular imaging [49]. The prof-of-principle of targeting and drug release is being investigated by attaching antibodies to DDS [50] and by applying radiation [51,52] or by thermal effects in the tissues [53,54]. Nanosystems like dendrimers, liposomes, niosomes, metal based NPs, micelles, nanoemulsions, quantum dots and polymer NPs have been developed (Table 2).…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…When functionalised with a targeting peptide these particles were used successfully to deliver paclitaxel to tumours exposed to 35 ionising radiation. 10 Yang et al reported the use of polyester/DNA nanoparticles to deliver the gene for vascular endothelial growth factor into stem cells to promote limb growth in mice, 11 and Palamoor and Jablonski exploited the gradual degradation of poly(orthoesters) for ocular applications, 40 achieving delivery of epinephrine over a period of several months. 12 Perhaps the most appealing feature of polyesters is for sustained (slow) release applications.…”
Section: Introductionmentioning
confidence: 99%
“…The principal aim of this study was to evaluate whether the nanoparticles would specifically disassemble in response to intracellular levels of GSH via reduction of the PDS solubility release catch. To verify a GSH-induced physical response, the 10 nanoparticles were held at 50 °C, GSH was added at 10 μM (extracellular) or 1 mM (intracellular) and the particle size measured. Addition of 10 µM GSH showed no changes visually, or by DLS.…”
mentioning
confidence: 99%